Analysis of foreign direct investments and investment attractiveness of Ukraine - Sheiko, I. А.; Kurdenko, O. V. (ХНУРЕ, 2021)
Foreign direct investment (FDI) is a significant part of international business and of the global economy. Companies that engage in FDI can expand to new marketplaces; shift their production facilities across national boundaries; and secure more advanced technologies, products, skills, and financing.
Keywords: foreign direct investment; стратегії економічного розвитку